Pemeliharaan Bahan Pustaka Khususnya Koleksi Karya Fiksi di Perpustakaan Umum Kota Solok - Hayat, Ihsanul; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
The research objective is to describe how the maintenance of a collection of works of fiction in Solok City Public Library. The data was obtained using the descriptive method, the technique of collecting data through observation or direct observation Solok City Public Library, and interviews with the librarian at the Public Library City Solok. From the data analysis and discussion, we can conclude the maintenance of a collection of fiction are: (1) clean room and dust barriers lack of adequate infrastructure, (2) give camphor or insect venom lack of budgetary constraints and lack of expertise, (3) setting collection irregular constraints on the shelf in the way of preparing the collection, (4) binding is not well done budgetary constraints and lack of expertise in binding activit Keywords: maintenance a collecti; works of fiction